Crop detection and control advisory system - Revesai, Ruvimbo (Midlands State University, 2019)
This research is aimed at developing a Crop Disease Detection and Control Advisory System which assists the farming community. The idea of developing the system came as a way of mitigating the problems affecting the organization that include poor and slow service delivery in FCC shops when assisting farmers or giving advice to farmers. Farmers from remote areas have to travel long distances to get assistance and be advised on how they can cure certain diseases affecting their plants and knowledge on how they can do their farming activities the best way. In a bid to solve these and some of the problems, the researcher came up with an idea of developing this system that allowed farmers to get knowledge and advice on their farming activities wherever they are and whenever they need it. The system allows a farmer to logon to the web system that will be available online anytime of the day. The proposed system was developed using PHP programming language and MySQL database. Farmers are provided with the best tips about their farming activities and advice on the best pesticides they can use to cure their crop diseases. Information was obtained from observations and questionnaires that enabled the development of the system to be a success. On completion, the system managed to enhance farmers in their farming activities allowing them to increase their production. On the other hand Consultants in the shops are finding work to be easier since they can assist farmers on their desktop machines. A system testing was also carried out to ensure that all user requirements were met.